2010
DOI: 10.1681/asn.2009090887
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the Kinin B1 Receptor Ameloriates Glomerulonephritis

Abstract: Severe inflammation characterizes rapidly progressive glomerulonephritides, and expression of the kinin B1 receptor (B1R) associates with inflammation. Delayed B1R blockade reduces renal inflammation in a model of unilateral ureteral obstruction, but whether B1R modulates the pathophysiology of glomerulonephritides is unknown. Here, we observed an association of B1R protein expression and inflammation, in both glomeruli and the renal interstitium, in biopsies of patients with glomerulonephritides, HenochSchö n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 37 publications
2
50
0
1
Order By: Relevance
“…Most published studies have focused on the phase of acute glomerular injury (which may be associated with impaired renal function in association with crescentic disease), while data on long-term follow-up to determine if the mice develop progressive tubulointerstitial fibrosis, tubular atrophy and renal insufficiency are sparse. Some studies have reported interstitial inflammation [5961] and elevated serum creatinine levels but the latter are likely a consequence of severe glomerular damage [62, 63]. Our preliminary studies with NTS generated by the Shankland laboratory suggest that progressive tubulointerstitial disease requires repeated NTS injections [64].…”
Section: Alternative Mouse Ckd Modelsmentioning
confidence: 99%
“…Most published studies have focused on the phase of acute glomerular injury (which may be associated with impaired renal function in association with crescentic disease), while data on long-term follow-up to determine if the mice develop progressive tubulointerstitial fibrosis, tubular atrophy and renal insufficiency are sparse. Some studies have reported interstitial inflammation [5961] and elevated serum creatinine levels but the latter are likely a consequence of severe glomerular damage [62, 63]. Our preliminary studies with NTS generated by the Shankland laboratory suggest that progressive tubulointerstitial disease requires repeated NTS injections [64].…”
Section: Alternative Mouse Ckd Modelsmentioning
confidence: 99%
“…Quantification was performed as described previously. 67 induced generation of PAI-1 and fibrin formation, key mediators of decreased kidney perfusion and oxygenation. 43 …”
Section: Effect Of Preconditioned Nanofibers On Lps-induced Rho Kinasmentioning
confidence: 99%
“…While the mechanisms of acute NTS are more completely characterized than the later autologous phases, the acute NTS model of glomerular injury remains complex due to evidence of multiple targets in the glomerulus including decay accelerating factor [28], CD59 [29], and others [30][32]. Using mice backcrossed over 10× to C57BL/6, we injected PodΔ Myh9 (KO) mice versus DHet control and FF control littermates with sheep NTS (graciously provided by Dr. D. Salant) or with control sheep IgG.…”
Section: Resultsmentioning
confidence: 99%